Rola biostymulacji mózgu w uczeniu się języka angielskiego przez nastolatków z niepełnosprawnością intelektualną w stopni lekkim - Płaksej, Anna (Neofilolog, 2011)
The 21st century is the time of dynamic development of advanced technol-ogies as well as creating and improving equal opportunities for those who have not had them so far. The appropriate and well adjusted education of people who are mentally retarded may turn out to be one of the most im-portant ways to prepare them to live independently in their societies. In every Polish school at least one foreign language is taught and mostly it is English. Even though the idea of teaching English to mildly retarded stu-dents has always been controversial, the Ministry of Education in Poland decided to put it into practice. Consequently, since 2009 the junior high school graduation exam has included a component devoted to testing a for-eign language. These changes made it necessary to increase the effective-ness of foreign language pedagogy.